Efektivitas Teknik Problem Solving untuk Menurunkan Perilaku Prokrastinasi Akademik Peserta Didik Kelas X IIS 3 SMAN-1 Palangka Raya: The Effectiveness of Problem Solving Techniques to Reduce Academic Procrastination Behavior of Students in IIS 3 Class X-1 Palangka Raya - Apsabra Apsabra; Karyanti Karyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The purpose of this study is to find out that problem-solving techniques can reduce academic procrastination behaviour towards students of class X The population in this study were all students of class X IIS 3 of SMAN-1 Palangka Raya. The number of initial research samples consisted of 8 and finally only seven students. Sampling is determined by purposive sampling technique. Data collection techniques used observation, interviews, and the scale of procrastination behaviour. The method used is pre-experiment, data analysis techniques using Paired Sample T-Test or better known as Pre-Post Design is an analysis involving two measurements on the same subject to a particular influence or treatment. Based on the results of the study and discussion above, it can be concluded that the problem-solving technique can reduce the behaviour of academic procrastination of students in Class X of IIS-3 of SMAN-1 Palangka Raya. This is based on the results of the Paired-Sample T-Test, obtained t count = 6.264 can be concluded that there are differences in the level of procrastination before and after treatment. Procrastination behaviour has decreased from the initial average of 147.78 to 164.78. It means